A VALIDATION OF TECHNOLOGY ACCEPTANCE MODEL IN MEASURING ACCEPTANCE OF E-FILING TAXPAYERS - Ilias, Azleen; Abdul Razak, Mohd Zulkifli; Yasoa, Mohd Rushdan; Mohd Suki, Norazah Bte (International Business Education Journal, 2011)
This study attempts to validate technology acceptance model (TAM) factors for measuring e-filling taxpayers’ acceptance particularly in Malaysia. Data are collected from 100 taxpayers in three higher learning institutions in Labuan FT. Factor analysis is employed in this study to measure and validate TAM factors ( attitude, behavior intention, information quality, information system quality, perceived credibility, perceived ease of use, and perceived usefulness) which contribute to e-filing acceptance by Malaysian taxpayers. The finding of this study verifies that tam instrument is still valid in measuring the acceptance of e-filing among taxpayers. We found that most of the factor loading for each item above 0.7, which support the TAM model previously adapted by Chang et, al., (2005). The implication of this study suggests that Inland Revenue Board can confidently apply the instrument in measuring e-filing acceptance among taxpayers.